2009
DOI: 10.1074/jbc.m900393200
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Selection of Kinase-responsive RNA Elements Controlling Alternative Splicing

Abstract: Alternative pre-mRNA splicing is often controlled by cell signals, for example, those activating the cAMP-dependent protein kinase (PKA) or the Ca 2؉ /calmodulin-dependent protein kinase IV (CaMKIV). We have shown that CaMKIV regulates alternative splicing through short CA repeats and hnRNP L. Here we use a splicing reporter that shows PKA/CaMKIV promotion of exon inclusion to select from exons containing random 13-nt sequences for RNA elements responsive to the kinases in cultured cells. This selection not on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…These reporters were transfected into HEK293T cells, and their responses to coexpressed Flag-PKA or its kinase-dead mutant Flag-PKAm, as used previously (32), were examined by semiquantitative RT-PCR. From these preliminary tests, the only observed effect that is consistent with the endogenous exon changes in PC12 cells was a repression by PKA in several reporters containing exon 5a only (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…These reporters were transfected into HEK293T cells, and their responses to coexpressed Flag-PKA or its kinase-dead mutant Flag-PKAm, as used previously (32), were examined by semiquantitative RT-PCR. From these preliminary tests, the only observed effect that is consistent with the endogenous exon changes in PC12 cells was a repression by PKA in several reporters containing exon 5a only (Figure 1D).…”
Section: Resultsmentioning
confidence: 99%
“…Apart from regulation of transcription, little is known about the function of the C subunit in the nucleus. It is known that PKA phosphorylates several splicing factors and is involved in the pre-mRNA splicing (30,38,39). We recently found that in AD brain, the activity of PKA is down-regulated as a result of proteolysis of the regulatory subunit by over-activated calpain I (40).…”
mentioning
confidence: 99%
“…Furthermore, coexpression of PKA dramatically elevated phosphorylation levels of these two transcriptional activators. In contrast, the PKA dead kinase (K73E and K169E) (46) failed to promote phosphorylation of both CLOCK and BMAL1 in the same procedure of experiments ( Fig. 3B).…”
Section: Both Clock and Bmal1 Are Pka Targets And Cnot1 Promotes Assomentioning
confidence: 72%